ELEMENTARY PARTICLES, ATOMIC NUCLEI AND MOLECULES ACCORDING TO THE BSM – SUPERGRAVITATION UNIFIED THEORY: ELEMENTARY PARTICLES, ATOMIC NUCLEI AND MOLECULES ACCORDING TO THE BSM – SUPERGRAVITATION UNIFIED THEORY - Sargoytchev, Stoyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The Basic Structures of Matter – Supergravitation Unified Theory (BSM-SG) is based on alternative concept of the physical vacuum. At small distance below 1 angstrom the Supergravitational forces appear as strong nuclear forces, while at larger distance they converge to the Newtonian gravity. Amongst the major outcomes from BSM-SG theory are derived material structures of the stable elementary particles forming the material structure of atomic nuclei. The protons and neutrons are not spherical but having a shape of twisted and folded torus, respectively. They are thin but with much larger size than the size of the atomic nuclei according to the QM models, so the Coulomb field is not converged to a size in the order of 10E-15 m but is distributed over much larger size of the proton. The BSM-SG models of nuclear structures exhibit an excellent match to the pattern of Periodic Table, showing signatures of valences, Pauli Exclusion Principle and Hunds rule. They also define the angular restrictions of the chemical bonds.